A brief survey of the development of Turkish library catalogues - (:unkn) unknown (K G SAUR VERLAG KG, 2001)
Previous articles have dealt with various aspects of the Ottoman library system including the catalogues of the collections. However, since their publication, new material has come to light and this is now the opportune moment to review the development of cataloguing, from the foundation of the first Ottoman libraries to the present century. In this article, Turkish library catalogues and cataloguing shall be dealt with in three distinct periods. The first period covers the history of cataloguing from the very beginning to the second half of the 19(th) century, dealing in particular with three of the earliest catalogues, dating from the 16(th) century. The second period deals with the attempts to prepare union catalogues of the collections in the libraries of Istanbul, together with the appearance of the first printed catalogues for individual libraries. The third is the Republican period, covering the seven decades from 1923 to the present day.